Biological Variation of Erythrocyte Total, Metal-Free, and Zinc Protoporphyrin IX in Patients with Erythropoietic Protoporphyria and Healthy Subjects: Implications for Clinical Interpretation and Monitoring. - Lillemoen, Paul Kjetel Soldal; Fauskanger, Pernille Kjeilen; Sandberg, Sverre; Aarsand, Aasne Karine (Clinical Chemistry, 2025)
Background There is a lack of robust biological variation (BV) data for porphyria-related biomarkers. Our study aimed to estimate BV of erythrocyte total, metal-free, and zinc protoporphyrin IX in patients with erythropoietic protoporphyria (EPP) and healthy subjects and to explore the clinical implications of these data. Methods Fourteen patients with EPP and 15 healthy subjects were sampled quarterly for 2 years, and erythrocyte protoporphyrin analyses were performed in duplicate in all samples. A Bayesian method was used to estimate the within-subject (CVI) and personal (CVP(i)) BV. Results Based on clinical and laboratory assessments, EPP patients were stable during the study, with only 2 data points excluded. CVI in the EPP cohort was estimated as 9.8% (95% credible interval 8.5%–11.5%) for erythrocyte total protoporphyrin, 10.5% (9.0%–12.3%) for metal-free protoporphyrin, and 5.9% (4.3%–8.0%) for zinc protoporphyrin. Baseline metal-free protoporphyrin ranged from 6.9 to 139.8 µmol/L, but the CVP(i)s derived for each patient were similar (20th and 80th percentile of predicted distribution 9.5%–11.5%), and data were homogeneously distributed. Metal-free protoporphyrin was not measurable in the healthy cohort. Data for zinc protoporphyrin were heterogeneously distributed in both study cohorts. Conclusions The EPP patients had different set points for metal-free protoporphyrin, but the CVP(i) was similar, supporting the use of the same treatment goals when monitoring. This study is the first to use Bayesian analysis to demonstrate that personal BV is similar in patients with stable, chronic disease and different set points.